"I would never wear those old clodhoppers!": Age differences and used clothing consumption in the Czech Republic. (May 2020) - Rulikova, Marketa
The article explores secondhand clothing dynamics in the Czech Republic as evidence of the shifting material culture and moral economy in this post-socialist country. Ethnographical investigation indicates that the practices and meanings surrounding the Czech market in used clothing are quite distinct from what has been observed elsewhere in the world of reused clothes. The case study notes a significant contradiction between widespread participation in the shopping for and wearing of secondhand clothing, and concurrent concealment of such practice among Czechs. This seeming contradiction can be largely attributed to the attraction for inexpensive branded clothes, which helps signal an individual's well-being and search for respect in a newly competitive market society, and the simultaneous association of reuse with the backwardness and consumer poverty associated with the socialist era. The contrast in values and norms surrounding the acceptability of used garment is especially pronounced in different generations. It is argued here that membership in generations should be considered a more significant variable than class or other social attributes in dissecting social differences in transitioning societies.